The Sleepy Hollow mystery - Warner, Gertrude Chandler, 1890-1979 (Warner, Gertrude Chandler, 1890-1979. Boxcar children mysteries, 2015)
"In the town of Sleepy Hollow, the Aldens discover an old legend that's come back to life! Their friend's ghost-tour business is being disrupted by a spooky figure on horseback who throws pumpkins in the streets and frightens everyone. Has the headless horseman returned to haunt the town? The Boxcar Children must find out before the ghost tours are ruined!"--Jacket flap.